Metadata and its impact on libraries - Intner, Sheila S (Libraries Unlimited, 2006)
In recent years, metadata (data about data) has been the subject of countless discussions, research projects, and articles. This useful book does much to clarify the distinctions and complexities of the subject. Part 1 of the text opens with various definitions of metadata, defining its scope, focus, and division into categories. Subsequent chapters discuss library and information-related metadata schemas, specifying how to create library metadata for monographs and continuing resources, including their integration into local catalogs and databases. Part 2 is devoted to archiving and preserving digital materials, focusing on the impact on library services and future possibilities. The writing throughout the book is clear and supported by copious citations, figures, and screen shots. Two chapters boast sample exercises with answer keys, allowing readers to try their hand at cataloging and classifying metadata. Overall, a fine work that has much to recommend it